The Future of Information Literacy in the Library: An Example of Librarian/Publisher Collaboration. Issue 1 (1st May 2017) - Donlan, Rebecca; Stanislaw, Stacy; Fernandez, Michael
ABSTRACT: As information sources have expanded, there have been parallel changes in the way students and researchers find and use that information. The role of the library has shifted to embedding information literacy skills into the curriculum as a primary function. This presentation explored how librarians are becoming more involved with information literacy curriculum and how publishers can assist them, particularly regarding access to information and the scholarly publishing process. Since 2015, Rebecca Donlan at Florida Gulf Coast University (FGCU) and Stacy Stanislaw at Taylor & Francis Group have been collaborating on an information literacy program for FGCU students and faculty that focuses specifically on navigating the scholarly publishing landscape. Donlan and Stanislaw provided an overview of the project, its formation, implementation, and progress to date.